This book is not good for you - Bosch, Pseudonymous (London Usborne Publishing, 2009)
Cass, Max-Ernest and Yo-Yoji, members of the top-secret Terces Society, are on a mission to track down a cursed Aztec tuning fork that has the power to recreate any flavour its user has ever tasted. But when an evil chef uses the fork to create a deadly chocolate recipe, and tricks Cass and Yo-Yoji into eating it, only Max-Ernest can save the day.
Keywords: Children Mystery Book; Non-fiction